TRIPLE ENTRY ACCOUNTING: KAJIAN LITERATUR TERHADAP PERKEMBANGAN SISTEM PENCATATAN BERBASIS BLOCKCHAIN - Deby Arachel Arta Viola; Ita; Nurul Latifa Azis; Fricilya Orpi Putri; Muh Fadly; Nur Asliana; Nurafni Oktaviyah (ISAFIR: Islamic Accounting and Finance Review, 2025)
The traditional double-entry accounting system has begun to reveal critical limitations in mitigating information asymmetry and data manipulation in the digital era. This study aims to explore the paradigm evolution toward blockchain-based Triple Entry Accounting (TEA) as a solution for strengthening financial reporting transparency and integrity. Employing a Systematic Literature Review (SLR) method supplemented with bibliometric analysis, this study examines 47 reputable journal articles from Scopus and Google Scholar databases (2017–2025). The literature synthesis indicates that the integration of distributed ledgers and cryptography in TEA creates an immutable single source of truth, thereby minimizing the need for manual reconciliation. Furthermore, automation through smart contracts facilitates the transition from periodic auditing to real-time continuous auditing, which significantly prevents accounting fraud. Despite offering absolute accountability, TEA implementation in developing countries like Indonesia is still constrained by high infrastructure costs, regulatory vacuums, and the digital literacy gap. This article concludes that TEA is not merely the digitalization of records, but a governance revolution that demands the readiness of a comprehensively integrated technological ecosystem.